Extending SAP TM Freight Unit Type Determination: A Custom Determination Class Architecture for Multi-Criteria Transportation Planning - Bhanu Chander Keerthi (International Journal of Intelligent Systems and Applications in Engineering, 2026)
Freight Unit type determination in SAP Transportation Management is the upstream decision that governs carrier selection, mode of transport record assignment, and freight order creation for every outbound delivery. Standard TM determination evaluates only source location, destination location, and incoterm — criteria that cannot differentiate between insourced, outsourced, and customer pick-up fulfilment channels when those channels share physical locations but differ in sales area structure. This article documents ZCL_COND_SO_DLV_EXTR, a custom ABAP OO determination class that extends the standard /SCMTMS/CL_COND_SO_EXTR by extracting sales organisation, distribution channel, division, delivery type, and transportation zone from the underlying sales order and delivery document at FU creation time. These five attributes, combined with the standard source and destination location criteria, populate a seven-parameter BRF+ decision table (ZTOR_FU_TYPE_DET) assigned to freight unit building rule ZFUBR_01, enabling three-channel FU type resolution. Deployed at a large US healthcare distributor, the architecture reduced incorrect FU type assignment from 23% to 0.6% of deliveries, eliminated recurring freight order exceptions averaging 2.1 per shift, and delivered an annual operational saving of USD 410,000 (Author’s primary implementation data, 2023). The design contribution is a documented copy-and-extend determination class pattern with BRF+ decision table governance — applicable to any SAP TM site requiring sales-area-driven FU type differentiation.